2001
DOI: 10.1164/ajrccm.164.3.2005003
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ventilator-associated Pneumonia by Oral Decontamination

Abstract: cross infection, prevention and control; respiration, artificial, adverse effects; antibiotics, administration and dosage infection control methods; pneumonia, etiology, prevention and control; intubation, intratracheal, adverse effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(70 citation statements)
references
References 26 publications
1
64
0
5
Order By: Relevance
“…Although our sample size was small, these results are suggestive of a population of high-risk patients. In a prospective, randomized, double-blind, placebocontrolled study of 226 patients, Bergmans et al 4 found that oropharyngeal colonization was a key component in the development of VAP among ICU patients. The variation in the reported rates of VAP may partially reflect the heterogeneity of patients in different types of ICUs.…”
Section: Ventilator-associated Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Although our sample size was small, these results are suggestive of a population of high-risk patients. In a prospective, randomized, double-blind, placebocontrolled study of 226 patients, Bergmans et al 4 found that oropharyngeal colonization was a key component in the development of VAP among ICU patients. The variation in the reported rates of VAP may partially reflect the heterogeneity of patients in different types of ICUs.…”
Section: Ventilator-associated Pneumoniamentioning
confidence: 99%
“…1 The combination of poor oral health and airway devices may increase the risk of ventilator-associated pneumonia (VAP). 4,5 The rates of morbidity and mortality associated with VAP range from 20% to 41% in various intensive care units (ICUs).…”
mentioning
confidence: 99%
“…(1,3,7,19,20) Evidence has correlated microbial colonization of the oropharynx and of the dental plaque with VAP. (1,2,6,7,9,11,12,16,17,19,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) Almost 50% of the healthy adults present aspiration of oropharyngeal secretion at some point during sleep; this percentage increases to 70% in cases of patients with a drop in the level of consciousness. (1,3,19) When the respiratory conditions of the patient worsen to the point of requiring intubation, resources such as MV can lead to the risk of microaspiration of pathogens to the lower respiratory tract.…”
Section: Pathogenesis Of Nosocomial Pneumonia and Importance Of The Omentioning
confidence: 99%
“…(33) A decrease of up to 40% in cases of pneumonia was observed when oral hygiene of patients was mechanically and chemically improved. (20) The efficacy of the combination of chlorhexidine and other antimicrobials, such as neomycin sulfate, gentamicin or vancomycin, has also been reported.…”
Section: Prevention Of Nosocomial Pneumonia: Importance Of Oral Hygiementioning
confidence: 99%
“…In einer weiteren Untersuchung an herzchirurgischen Patienten konnten die Häufigkeit respiratorischer Infektionen und der Antibiotikaverbrauch durch orale Spülung mit 0,12%igem Chlorhexidin gesenkt werden. Die oben genannte Untersuchung von Bergmans et al [3] unterstreicht deshalb nachdrücklich die Bedeutung der oropharyngealen Dekontamination. Es bleibt aber weiterhin unklar, ob die zusätzliche gastrale Applikation von SDD weitere Vorteil erbringt, da eine direkte Vergleichgruppe in dieser Studie fehlte.…”
Section: Bewertung Der Pneumonieprävention In Metaanalysenunclassified